The Role of Organizational Structure as a Mediator In the Relationship between Information Technology and both Decision Making and Organizational Communication: Empirical Study on Selected Iraqi Ministries - Kadhim, Wisam; Al-Abrrow, Hadi (The Arab Journal of Administration, 2018)
The study focused on knowing «the role of the organizational structure as a mediator in the relationship between the information technology and both decision making and organizational communicationa.» This study introduced a comprensive theoretical model which included independent variable (IT) which consist of of a number of dimensions (components material, software, data, network, human resources), and changing the mediator (organizational structure) dimensions (official, central, complex), and finally, the two variables followers, the first (decision-making) dimensions (of tasks and responsibilities, logical, social, political), The second variable is represented by (Organizational Communication) four dimensions (the official books, e-mail, meetings, internal network. The study was conducted in a number of ministries and of the Ministry of Higher Education and Scientific Research, the Ministry of Planning, the Ministry of Finance, Ministry of Education, and finally, the Ministry of Housing and Construction. The study questionnaire as an essential tool for data collection in the practical side, having been Poll 160 managers, and after excluding the damaged ones, the number of valid questionnaires for analysis of 131 questionnaire, as well as personal interviews, has been the normal distribution of the test data, and the analysis and description and diagnosis The study variables and test correlations and identify the direct and indirect effects among variables of the study. The study set of conclusions, including: to the organizational structures of the ministries under the search response to information technology within their organizational structures, as well as shown by the indicators of the impact of information technology on the dimensions of the organizational structure, which in turn indirectly affect other axes. The results showed a relationship between information technology and decision-making dimensions, where with the use of information technology enables managers to give a more accurate decisions and speed. The results showed the existence of the relationship between information technology dimensions and contact the organization, where information technology to increase the volume of information transmitted and the possibility of disseminated to the widest ranges and time is very short, and included the delivery of instructions and procedures among the ministry’s headquarters and departments affiliated scattered geographically to all provinces.